Theatre and Democracy Building Democracy in Post-war and Post-democratic Contexts - Janse van Vuuren, Petro; Rasmussen, Bjørn; Khala, Ayanda (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
Theatre and Democracy: Building Democracy in Post-war and Post-democratic Contexts is the outcome of a longstanding collaboration between two centers of applied theatre education and research in South-Africa and Norway, respectively (2017-2022). It presents knowledge, critical conversations and artistic work related to issues of democracy, both historical and contemporary. Within the global framework of our current (post)democracies, thirteen chapters contain stories and analyses from artists and researchers who all study, understand and facilitate theatre as a political-performative medium in dealing with community-specific democratic issues. The reader encounters studies and reports from specific cases of applied theatre, community culture development and performance activism in countries such as South-Africa, Pakistan, Zimbabwe and Norway. There is a common interest in theatre as a platform for active citizenry, as well as several attempts to explore theatre as a platform for "political subjectivation" (Rancière).